2016
DOI: 10.11648/j.ajns.20160503.12
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Nursing Intervention Program on Emotional Distress, Self-Efficacy, and Liver Enzymes Among Hepatitis C Virus Patients Undergoing Antiviral Treatment Therapy (Sovaldi Medication)

Abstract: Almost all patients receiving hepatitis C antiviral therapy will experience some treatment-related adverse effects.Emotional distress and fatigue can lead to early treatment discontinuation. Close monitoring is crucial throughout treatment. The nurses can promote adherence by counseling patients on the recognition and management of treatment-related adverse effects. The purpose of the study was to evaluate the effectiveness of nursing intervention program on emotional distress, selfefficacy and liver enzymes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…The AMAEP for patients with CHC also improved patients’ self-efficacy in taking antiviral drugs compared with the control group, which is similar to the results of previous studies [ 9 , 35 , 36 ]. This may be because this program recognized the need for antiviral drugs and confirmed the treatment goals through education, which improved patients’ understanding of the disease.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The AMAEP for patients with CHC also improved patients’ self-efficacy in taking antiviral drugs compared with the control group, which is similar to the results of previous studies [ 9 , 35 , 36 ]. This may be because this program recognized the need for antiviral drugs and confirmed the treatment goals through education, which improved patients’ understanding of the disease.…”
Section: Discussionsupporting
confidence: 89%
“…Self-efficacy is the main variable in medicine administration and patients with higher self-efficacy tend to be more efficient in adhering to their treatment, which affects the treatment results [ 7 ]. Since not taking medication leads to discontinuation of the treatment, it is important to actively monitor the treatment process, particularly medication use among patients [ 8 , 9 ]. Misuse has been defined as the incorrect use of an over-the-counter (OTC) product for a medical purpose, usually in regard to dosage or duration of use [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by Sabola et al, (2022) who found that there was an improvement in all mean score of patients' laboratory data. Also, these results are consistent with Malky et al, (2016) who indicated highly significant reduction of liver enzymes post intervention than pre-intervention.…”
Section: Knowledge Assessment For Studied Groupssupporting
confidence: 89%
“…Clinical nurses have regular contact with patients in outpatient clinics and hospital wards. The physical and psychological support clinical nurses provide to hepatitis C patients receiving antiviral treatment has been found to have a positive effect, as it increases adherence to medication (23,24). Previous studies have shown that educational interventions by clinical nurses have helped patients increase their understanding of hepatitis C and improve their QOL (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%